From Social Pacts to Productivity Boards - Philippe Pochet (Intereconomics, 2016)
Market solutions can be a way for small deregulated states like the Baltics to grow, but they are not a viable path for the EMU area as a whole or for the larger countries like France, Germany or Italy. As most of the challenges have to be addressed at the national level only, an interaction of flexible institutions (as the social pacts were) in coordination with developing European institutions (like a European unemployment scheme) can offer a more stable environment for growth.
Keywords: 330